Cell protective effects of vitamin C against oxidative stress induced by ciprofloxacin on spermatogenesis: involvement of cellular apoptosis - Ibrahim, Nihal A.; Buabeid, Manal A.; Elmorshedy, Kadreya E.; Arafa, El-Shaimaa A. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionCiprofloxacin (CPFX), a second-generation fluoroquinolone, is widely used as an anti-infective agent for genitourinary tract infections due to its broad-spectrum efficacy against gram-positive and gram-negative organisms. Although CPFX is considered safe at therapeutic doses, recent evidence suggests its potential biological toxicity, particularly affecting testicular histology and function. This study aimed to investigate the effects of CPFX on testicular structure and function and to evaluate the protective role of vitamin C.MethodsForty adult male albino rats were divided into four groups: control, CPFX-treated, vitamin C-treated, and CPFX combined with vitamin C-treated. After 60 days of treatment, blood samples were collected for hormonal assays, while testicular and epididymal tissues were analyzed using light and electron microscopy. Oxidative stress markers, including malondialdehyde (MDA), glutathione (GSH), and catalase (CAT) enzyme activity, were assessed. Statistical analyses were conducted using SPSS software.ResultsConfocal microscopy of the CPFX-treated group revealed significant reductions in germ cell populations within seminiferous tubules, accompanied by severe apoptosis and degenerative epithelial changes. Morphometric analysis confirmed a decrease in tubular diameter and epithelial height, degeneration of spermatogenic cells, and detachment of apoptotic cells from the basement membrane. CPFX treatment significantly reduced testosterone levels and induced variable changes in gonadotropin hormones (LH and FSH). Co-administration of vitamin C with CPFX restored normal testicular morphology, preserving seminiferous tubule integrity and maintaining spermatogenic cell populations and spermatozoa within the lumen.Discussion and ConclusionVitamin C supplementation effectively mitigated CPFX-induced oxidative stress by significantly reducing MDA levels and enhancing antioxidant defenses, including increased GSH content and CAT enzyme activity. These findings highlight the therapeutic potential of vitamin C in reversing CPFX-induced testicular toxicity by alleviating oxidative stress and restoring testicular function.